Property evaluation of second generation biodiesel for gas turbine application - Muthaiyah G.; Palanisamy K. (Italian Association of Chemical Engineering - AIDIC, 2023)
Alternative fuels; Crude oil; Distillation; Fatty acids; Gas chromatography; Gas oils; Gas turbines; Gases; Proven reserves; Viscosity; Crude oil resources; Distillation method; Gas turbine applications; Oil reserves; Petroleum costs; Property; Property evaluation; Renewable energies; Renewable fuels; Second-generation biodiesels; Biodiesel